Cucurbit[6]uril as a functional monomer in molecularly imprinted polymers: synthesis, structural and thermal characterization - Chuin, Lim Xiang; Thangaraja, Karthiyaani A/P; Praveena, Sarva Mangala; Yahaya, Noorfatimah; Johari, Ili Syazana; Tejo, Bimo Ario; Kamaruzaman, Sazlinda (Springer Science and Business Media B.V., 2025)
In a groundbreaking approach, Cucurbit[6]uril (CB[6]) has been successfully incorporated as a functional monomer to synthesize molecularly imprinted polymers (MIPs) through bulk polymerization, opening new avenues for advanced material development. Methacrylic acid (MAA) was used as a second monomer, with dimethylformamide (DMF), ethylene glycol dimethacrylate (EGDMA), and ammonium persulfate (APS) serving as the porogen, crosslinker, and initiator, respectively. In this study, two CB[6] to MAA ratios (MIP 1:80 and MIP 1:100) were tested, aiming for selectivity toward atrazine (AT) in aqueous media. The structure of the MIPs was analyzed using field emission scanning electron microscopy (FESEM), energy dispersive X-ray (EDX), X-ray diffraction (XRD) analysis and Fourier-transform infrared spectroscopy (FTIR), confirming that CB[6] was successfully polymerized. XRD analysis confirmed the amorphous nature of both MIPs, while FESEM revealed rough, wrinkled, and folded morphology. MIP 1:100 exhibited a rougher surface with less uniform pores than MIP 1:80. Thermal stability study demonstrated that increasing the MAA concentration reduces the polymer’s thermal stability. A preliminary adsorption study was conducted under specific conditions (pH 6, initial AT concentration: 10 ppm, adsorbent dosage: 20 mg, contact time: 120 min, and room temperature). MIP 1:80 showed higher removal efficiency (28.9%) than MIP 1:100 (17.2%), suggesting that these MIPs are suitable for adsorption studies and can be further enhanced by optimizing the ratio and adsorption conditions in future research. This novel polymer could have significant potential for applications in selective adsorption, catalysis or as a sensor due to its unique structure and thermal properties.